Wood Construction Practices of the Dong Ethnic Group (Guangxi Province, China) - Wei Wu; Xun Liu (Prostor, 2024)
This exploratory multiple-case study aims to analyse the ecological design of wooden houses in Dong villages (Guangxi province, China). Residential and public Dong houses were investigated from ecological and cultural perspectives. The results show that topography (i.e., building near the river in a mountainous area) is the main factor influencing the Dong building construction process. It also affects the building layout decisions. The life cycle assessment was applied to collect general information about the exterior and interior design of the Dong settlements. For this, a range of pictures and historical facts (e.g., demand for fire ponds and balconies, ornament usage, etc.) was analysed. The study suggests fir timber as a basic ecological resource for wooden house buildings. Yet, it is highly flammable and increases the fire risk. A brief discussion on the cultural heritage of the Dong people and its influence on their building system was presented. The present findings can be used in future eco-design projects as a brief guideline for creating a traditional-style ethnic wooden house.